Natal dalam Siklus Tahun Liturgi: Upaya Mengembalikan Makna Teologis di Tengah Pergeseran Praktik Perayaan - Silitonga, Oking Sahrul; Pasaribu, Azwar Anas (Sekolah Tinggi Diakones HKBP, 2025)
This paper discusses the meaning and importance of Christmas celebrations in the context of the liturgical year as the beginning of the pilgrimage of faith for Christians. The liturgical year includes a series of events that commemorate the life and teachings of Jesus Christ, with Christmas as one of the important celebrations. Using a descriptive-analytical qualitative method, this research collected data through literature study and observation. The results show that Christmas is more than just a religious celebration; Christmas as a one of the celebrations in the liturgical year marks the beginning of a pilgrimage of faith and reminds people of Jesus’s promise of salvation. The research highlights the importance of celebrating Christmas at the right time in the rhythm of the liturgical year to raise awareness of the pilgrimage of faith.